2020
DOI: 10.1007/s12529-020-09857-w
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Behaviors and Self-Esteem Among College Students: Systematic Review of Quantitative Studies

Abstract: Background Due to their impact on premature mortality and long-term disabilities, a better understanding of health risk behavior (HRB) determinants among college students is crucial in order to build the most appropriate prevention tools. Although selfesteem appears to be a relevant candidate, a clear picture summarizing its multiple links with HRB is lacking to guide clinicians and researchers. This study aims to provide a systematic review of the associations between health risk behavior and self-esteem amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 144 publications
(492 reference statements)
4
37
1
1
Order By: Relevance
“…A review of studies carried out between 2002 and 2014 on the habits of university students found that, on the whole, students do not have healthy eating habits, have a poor diet with a high intake of calories and excessive alcohol consumption, among other substances. These findings confirm the results of recent studies which show a wide range of high-risk behaviors among university students, including excessive alcohol consumption and poor eating habits [ 7 , 8 , 9 ]. In contrast, adherence to the Mediterranean Diet (AMD) is associated with better cognitive performance and emotional wellbeing [ 10 ].…”
Section: Introductionsupporting
confidence: 91%
“…A review of studies carried out between 2002 and 2014 on the habits of university students found that, on the whole, students do not have healthy eating habits, have a poor diet with a high intake of calories and excessive alcohol consumption, among other substances. These findings confirm the results of recent studies which show a wide range of high-risk behaviors among university students, including excessive alcohol consumption and poor eating habits [ 7 , 8 , 9 ]. In contrast, adherence to the Mediterranean Diet (AMD) is associated with better cognitive performance and emotional wellbeing [ 10 ].…”
Section: Introductionsupporting
confidence: 91%
“…Each of the three components of the identity resilience index has been shown individually to be instrumental in shaping reactions to health hazards (e.g. Arsandaux et al 2020;Hajek 2019;Hendy, Lyons, and Breakwell 2006;Schulenberg, Maggs, and O'Malley 2003). However, the significance of overall identity resilience in influencing such reactions has not been established.…”
Section: Identity Resiliencementioning
confidence: 99%
“…For example, Yuan et al 17 excluded self-esteem from their regression equation used for empirical analysis of self-perceived quality of life in Chinese patients with stoma. Arsandaux et al 18 further noted the high heterogeneity of variables used to measure selfesteem in the literature and the high heterogeneity of approaches used to validate and implement measures of self-esteem. Although studies of the role of self-esteem in health status and health prevention behaviors are inconclusive, they do suggest a positive link.…”
Section: Introductionmentioning
confidence: 99%